PROGRAM BLUE HEART CAMPAIGN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DI MEKSIKO TAHUN 2020-2021 - Saragi, Lyona Keren; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Human trafficking is a complex form of human rights violation, particularly in countries with high levels of social inequality like Mexico. One of the groups most vulnerable to this practice is indigenous communities, who are often marginalized both economically and politically. This study aims to analyze the implementation of the Blue Heart Campaign by the United Nations Office on Drugs and Crime (UNODC) in Mexico in 2020–2021 and assess the extent to which the program has reached victims from indigenous communities. By using document analysis method and a constructivist perspective, this study examines UNODC's role as an international actor in shaping norms and discourse on human trafficking. The results show that although the campaign has succeeded in raising public awareness of the issue on human trafficking, several limitations remain, such as a lack of ethnically disaggregated data and a lack of culturally sensitive strategies. Collaborative efforts between international organizations, governments, and local communities are needed to design more inclusive and responsive policies to human trafficking cases. Keywords: Human trafficking, UNODC, Blue Heart Campaign, indigenous communities, Mexico